Absence of modulatory effects of 6Hz cerebellar transcranial alternating current stimulation on fear learning in men - Schellen, Sarah Johanna; Zeidan, Philip; Ernst, Thomas M.; Thieme, Andreas; Nicksirat, Seyed Ali; Merz, Christian J.; Nitsche, Michael A.; Yavari, Fatemeh; Timmann, Dagmar; Batsikadze, Giorgi (Frontiers in Human Neuroscience, 2024)
Fear is a vital defense mechanism to potential threats, which is influenced by the cerebellum. While the cerebellum's role in acquiring fear responses is well understood, limited knowledge exists about its involvement in fear extinction. In this study, we investigated the effects of cerebellar theta band transcranial alternating current stimulation (ctACS) administered during fear extinction training, based on previous evidence from animal studies suggesting a role of cerebellar theta oscillations in associative memory formation. To this end, thirty-seven healthy right-handed male participants were recruited for a two-day differential fear renewal paradigm. On day 1, they underwent acquisition training in context A followed by extinction training in context B. On day 2, recall was tested in contexts A and B. One group of participants received ctACS in the theta band (6 Hz) during extinction training. The other group received sham ctACS. Although both groups demonstrated the ability to recall previously learned fear and distinguish between low and high threat stimuli, no significant differences were observed between the ctACS and sham groups, indicating that ctACS at this theta frequency range did not impact extinction and recall of previously acquired fear in this study. Nevertheless, using ctACS could still be useful in future research, including brain imaging studies, to better understand how the cerebellum is involved in fear and extinction processes.